Comparison of ocular surface assessment outcomes between healthy controls and patients with obstructive sleep apnea–hypopnea syndrome: a meta-analysis of the literature - Sun, Jian; He, Jie; Liang, Zongan (Frontiers in Physiology, 2023)
Objective: This meta-analysis aimed to determine whether or not ocular surface alterations are associated with disease severity in individuals with obstructive sleep apnea-hypopnea syndrome (OSAHS). Methods: The protocol for this systematic review and meta-analysis has been registered in PROSPERO. We searched six electronic databases (China National Knowledge Infrastructure, EMBASE, Cochrane Library, Web of Science, WanFang, and PubMed) from inception to December 30, 2022. Standard mean difference (SMD) and correlation coefficients were reported as measures of the effect size in the presence of retrieved data. In addition, either the random-effects or fixed-effects models were used in a combined analysis. Stata 11.0 and R 3.6.1 were used for the statistical analysis of the data. Results: Fifteen studies satisfied the requirements to be included in this study. Our analysis illustrated that the prevalence of floppy eyelid syndrome (FES) in OSAHS patients was 40% while that of dry eye syndrome was 48%. In addition, Schirmer 1 value and tear break-up time (TBUT) were remarkably reduced in OSAHS patients in contrast to those of the controls; ocular surface disease index (OSDI) scores, Oxford corneal staining scores, and the rates of loss in the meibomian glands were elevated in OSAHS patients as opposed to the controls, especially those with severe disease. Moreover, the Schirmer 1 value and TBUT exhibited a negative correlation with the Apnea-hypopnea index (AHI), and OSDI showed a positive association with AHI. Conclusion: Patients with OSAHS had a greater prevalence of FES, as shown in the existing data. Patients with OSAHS showed lower Schirmer 1 value and TBUT, higher OSDI, Oxford corneal staining scores, and the rates of loss in the meibomian glands as compared to healthy controls.